Afterload-related cardiac performance predicts prognosis in critical ill patients with sepsis: A prospective observational pilot study. Issue 38 (24th September 2021) - Zhao, Cong-Cong; Zhang, Li-Ru; Liu, Li-Xia; Sun, Li-Xiao; Hu, Zhen-Jie
Abstract : Abstract: To investigate the usefulness of afterload-related cardiac performance (ACP) for assessing cardiac impairment and predicting prognosis in septic patients. Adult patients with sepsis in the intensive care unit were included. Cardiac output, cardiac index, cardiac power index, and ACP were calculated at the time of admission (D0 ) and 48–72 h after admission (D3 ). They were correlated with Acute Physiology and Chronic Health Evaluation II and sequential organ failure assessment scores, then the prognostic values were analyzed. A total of 41 patients with sepsis were selected. ACP showed a stronger negative correlation with Acute Physiology and Chronic Health Evaluation II and sequential organ failure assessment scores than cardiac output, cardiac index, and cardiac power index. ACP predicted 28-day mortality with an area under the curve of 0.775 and 0.976 on D0 and D3, respectively. In addition, most non-survivors had emergent cardiac impairment (ACP ≤ 80%) on D0, and cardiac function was deteriorated on D3 . Survival analysis showed that the patients with a decreased ACP from D0 to D3 had the highest mortality. The decrease of ACP on D3 was an independent risk factor for mortality (hazard ratio, 11.89; P = .0028). ACP can be used to assess the severity of cardiac impairment in sepsis. Continued decline of ACP during the first 3 days strongly suggests a poor prognosis.